Validation of the ERS standard citric acid cough challenge in healthy adult volunteers - Wright, Caroline E (BioMed Central, 2010)
Protocols measuring cough sensitivity can vary in terms of nebuliser, tussive agent, single and dose response. A definitive method for measuring cough sensitivity needs to be established. The ERS guidelines recommend the KoKo DigiDoser (KD) delivery system. Study aim, was to compare the reproducibility of this citric acid (CA) cough challenge and previously established Mefar dosimeter (MD) protocol. 39 (female 26) volunteers mean age (40.4 yrs) were randomised to either KD or MD. Intra-day and inter-day reproducibility was compared. We calculated the concentration of citric acid evoking 2 coughs (C2). The geometric mean C2 (95%CI) was similar for both KD and MD, of 263 (200,339) mM and 209 (151,288) mM respectively. The mean KD C2 was not significantly different. (F = 0.807, p = 0.93) from baseline over 1, 2, and 4 hrs however, the MD demonstrated significant variability (F = 7.85, P < 0.001) Measuring mean log C2 at baseline and at 2 weeks, the KD demonstrated a stronger intraclass correlation of log C2 at baseline with 2 week log C2, ICC = 0.70 than was shown with the Mefar, ICC = 0.41 Administering CA from KD offers a reproducible cough challenge in healthy volunteers. The results correlate well with the MD challenge but offer greater intra-day and inter-day reproducibility. TRIAL REGISTRATION: Current controlled trials ISRCTN98385033